Good Governance, Social Capital and Political Trust - Iraj Ranjbar; Samira Golami (دولت‌پژوهی, 2022)
In this article, the aim was to explain the category of "political trust" and how it is created and accumulated in relation to "social capital". In this approach, trust as one of the components of social capital is not an inherent characteristic of individuals but an aspect of the conditions and environment in which individuals act. Thus, the source of social capital creation will vary in different societies with different levels of development. Long-standing traditions, local beliefs, and the efficiency of the political system, each alone or in combination, can be the source of social capital. The main argument of the present article is that only the kind of social capital that can create a lasting "political trust" that is born of the "good governance" model; Because this model, beyond "government", includes "civil society" and "capable individual-citizen" Which, by creating social capital in macro, medium and micro dimensions of the social system as a whole, indirectly lays the foundation for civil and rational political trust. In other words, only that type of social capital which is the product of corruption control, "rule of law", "responsibility", "transparency", external effectiveness, internal efficiency and free flow of information from the ruling political system can generate a kind of Political trust should be active and effective, and such factors are possible only in the light of a type of governance called "good governance". In this sense, good governance as a model consisting of an efficient government, an active civil society and individual empowerment and the dynamics of the private sector can be a generator of a special type of social capital with a civil and rational nature that is the necessary platform for provide stable "political trust".  In this structure, the relationships between governance components are horizontal and parallel. The components are mutually related to each other and the relationship is such that synergy and unity among actors is established in the drawing of macro-strategies. That is, in this sector, the structure of good governance is not hierarchical and its art is the interaction between social forces, i.e. market, government and civil society. The door of this structure is open for the decisions and implementation of general policies, while diversity and conflict of opinions, and the interactions are based on the needs and the main mechanism of the society. Therefore, good governance includes a set of formal and informal actors that influence the decision-making process, and most development institutions make the promotion of this model of governance an important part of their agenda. It is due to such characteristics that governance is defined as "directed influence in the social process" in which various mechanisms are involved. Some of these mechanisms are very complex and do not originate solely from public sector actors. Therefore, all the definitions of governance express a broader concept of government, which does not only include government actors and institutions, but also includes the three institutions of government, civil society, and the private sector. The government creates a political and legal environment, the private sector creates employment and income, and the civil society facilitates the political and social interaction of active groups to participate in economic, social and political activities. Therefore, the task of good governance is to provide the basis for cooperation and coordination between these three sectors as much as possible.Based on this, the main claim of the article, that is, the relationship between political trust and a certain type of social capital, is explained in the light of a "Meta-theoretical" model. That is, the relationship between good governance, social capital and political trust has been measured as a "theory". It is based on this three-sided triangle that the "rulers" must focus their minds on the paradigm shift that has occurred in the nature of policy making in the last decade of the 20th century and the beginning of the 21st century in order to deepen and institutionalize political trust. Based on such a change, political trust is often interpreted as people's feelings about political officials and their decisions. This means, when people think that politicians are moral, honest, trustworthy and faithful to their words, political trust is realized and if they think that political officials run the government for their own benefit and the interests of the majority they do not consider and are not truthful in their speech, trust in them decreases. However, in this article, the authors were of the opinion that political trust is not limited to people's confidence in political officials and the performance of government agents; Rather, political trust reflects people's assessment of the "political environment". In fact, people regulate a large part of their behavior in response to the environment and norms that they interact with continuously and perform their actions within their framework. If the game environment does not make trustworthiness and keeping promises beneficial to the members of the society and does not increase the cost of disregarding obligations and mutual trust, their willingness to offer these norms will decrease. In this way, political trust is not only the result of the behavior and speech of government officials in the field of reality or in the perception of the people, but the origin of its rise and fall should be sought in the category of "governance". As mentioned, "governance" includes "government" and includes the three elements of "government", "civil society" and "citizenship". Based on this theoretical arrangement Based on this theoretical arrangement, the claim of the authors was this that political trust is the product of the accumulation of "social capital" at three levels, "macro", "medium" and "micro", and such capital will lead to the production of "political trust". It was not only limited to evaluating the effectiveness of "government"; Rather, it should go beyond the act of government, arising from the model of "governance" in its good form, which is based on the three elements of "efficient government", "strong civil society" and "active individual-citizen". Finally, the method of collecting data in this documentary and library article and the method of judging and interpreting the collected information is also analytical and explanatory.